Different Chromosome Segregation Patterns Coexist in the Tetraploid Adriatic Sturgeon Acipenser naccarii - Stefano Dalle Palle; Elisa Boscari; Simone Giulio Bordignon; Víctor Hugo Muñoz-Mora; Giorgio Bertorelle; Leonardo Congiu (Diversity, 2022)
The Adriatic sturgeon, Acipenser naccarii (Bonaparte, 1836), is a critically endangered tetraploid endemism of the Adriatic region; it has been targeted, over the last 20 years, by different conservation programs based on controlled reproduction of captive breeders followed by the release of their juvenile offspring; its preservation would greatly benefit from the correct and coordinated management of the residual genetic variability available in the different captive stocks. In this sense, the setup of an efficient parental allocation procedure would allow identifying familiar groups and establishing informed breeding plans, effectively preserving genetic variation. However, being the species tetraploid, the analyses often deal with complex genome architecture and a preliminary evaluation of allele segregation patterns at different chromosomes is necessary to assess whether the species can be considered a pure tetraploid, as previously observed at some loci, or if a more complex situation is present. Here we study the segregation at 14 microsatellites loci in 12 familiar groups. Results support in different families the tetrasomic segregation pattern at 11 markers and the disomic segregation at three markers. The Adriatic sturgeon thus shows a mixed inheritance modality. In this species, and likely in other sturgeons, accurate knowledge of the loci used for paternity analysis is therefore required.